Portraying the Geography of US Airspace with 3-Dimensional GIS-Based Analysis and Visualization - Thi Hong Diep Dao; David G. Havlick (ISPRS International Journal of Geo-Information)
The United States identifies, monitors, and defends a vast network of controlled airspaces surrounding its own and allied territories. These controlled airspaces include civilian aviation classes (A through G), drone flying regions, and special use (military) air classifications. These controlled spaces are invisible to the naked eye and often go unnoticed. Managing and portraying data that function in two and three dimensions poses significant challenges that have hindered prior analyses or geovisualizations of controlled airspaces, but we demonstrate here how many of these can be surmounted to visually represent the spatial extent and patterns of US-controlled airspace. In this paper, we demonstrate how these complex spaces can be graphically represented and highlight how cartographic and geovisual representations of often-overlooked domains contribute to a richer understanding of the reach and character of US airspace. The methods described for this work can be extended to other types of multidimensional objects and may facilitate more robust considerations of how Geographical Information Science (GIS) can be useful in analyzing and depicting airspace and territorial claims in three dimensions.